Degradation of antibiotic sulfamethoxazole in aqueous media by UVA/TiO2 pure-brookite photocatalysis - Huy hoang, Do; Thi Hang, Ta; Thi Minh Thuy, Nguyen; Thi Thu, Bui; Van Hoi, Bui; Thi Thuong Huyen, Tran (Vietnam Journal of Science and Technology, 2022)
The appearance of antibiotic sulfamethoxazole (SMX) in natural environments poses a potential risk to human health and ecology. Among many developed treatment techniques to remove and degrade SMX from an aqueous environment, photodegradation using the phase-pure TiO2 nanoparticles (NPs) in brookite structure as an active photocatalyst could be considered as a novel and effective strategy. The photocatalytic degradation of SMX in aqueous media followed an apparent first-order kinetics under the simulated UV-A irradiation. The higher the photocatalysts load, the higher photocatalytic efficiency. The SMX photodegradation over brookite nanoparticles depended on the pH of the SMX solution that was related to changes in chemical isomers of SMX molecules in the range of pH values between 2.0 and 10.0. The degradation efficiency was highest at pH 10.0 (up to 88 % after 180 min under UV-A irradiation) when SMX was in anionic form. With real matrices, the presence of metal ions (in mineral water) and fact-finding organic matter (in surface water) had a small effect on photodegradation efficiency due to either the complexation between SMX with metal ions or the inhibition of free radicals. The obtained results confirmed that the nano-sized TiO2 brookite photocatalyst has a high potential for water and wastewater remediation.